Composite anti-disturbance control for stochastic systems with multiple heterogeneous disturbances and input saturation - Wei, Xinjiang; Dong, Lewei; Zhang, Huifeng; Han, Jian; Hu, Xin (ISA transactions, 2020)
This paper develop a novel composite anti-disturbance control (CADC) method for a class of stochastic nonlinear systems in which input saturation and multiple heterogeneous disturbances occur. The disturbances include additive white noise, multiplicative white noise and modeled disturbances with coupling of energy-limited white noise and state signals. The input saturation item of system is approximated by the polytopic bounding method. In order to estimate the modeled disturbances, a novel stochastic saturating disturbance observer (SSDO) is designed. The CADC scheme is presented by integrating SSDO with convex hull expression of saturated linear feedback law, such that the superior anti-disturbance performance to be achieved while overcoming the effects of input saturation. Finally, the validity and usability of the developed scheme are testified by the numerical simulation and practical application example. •The CADC strategy is proposed to deal with saturation problem of stochastic systems.•The modeled disturbance with coupling of white noise and system states is considered.•Saturation term is introduced into disturbance observer to ensure superior estimation performance.